Influence of a suspended aid on wrist loading pattern during circles on pommel horse - Fujihara, T.; Gervais, P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to investigate the influence of a suspended aid on the reaction forces during a basic skill on pommel horse. Twenty gymnasts performed three sets of 10 circles with and without a suspended aid on a pommel horse under which two force plates were set. The results confirmed that the suspended aid could reduce the magnitude of the pommel reaction forces during circles while maintaining the general loading pattern. The average force, peak force, and impact force were all reduced by the use of the aid. A suspended aid may be useful for all levels of gymnasts who would like to practice pommel horse exercises with reduced wrist loading for a purpose such as a progression for learning a new skill, control of training volume or rehabilitation.